Bioenergy production from sunflower husk in Ukraine: potential and necessary investments - Horak, Jakub; Bilan, Yuriy; Dankevych, Andrii; Nitsenko, Vitalii; Kucher, Anatolii; Streimikiene, Dalia (My University, 2023)
Sunflower is a strategic crop in the agriculture of Ukraine as it is important for food and energy production. Recently the processing of secondary products, solving the issues of waste disposal and improving the environment have been paid much attention. This is an example of a cyclic economy, as during the production of oil from sunflowers, their husk can be used for energy production. The ash obtained by burning husk is a valuable complex mineral fertilizer and can be further applied as ecological fertilizer. The aim of this article is to assess the energy and investment potential for sunflowers as an internal reserve for increasing production efficiency and reducing carbon dioxide emissions. In particular, the equivalents of energy substitution of sunflower husks for energy costs at fat-and-oil enterprises, the reduction of carbon dioxide emissions are estimated. A generalized scheme for the production of electricity from sunflower husks is considered. In particular, the use of ash from sunflower husks as a fertilizer is described. The research has shown that the sunflower husks available in Ukraine can be used more efficiently to produce electricity. Therefore policy recommendations were developed based on a study conducted

Соняшник є стратегічною культурою в сільському господарстві України, оскільки має продовольче значення і виробництво енергії. Останнім часом переробка вторинної продукції, вирішення питання відходів утилізації та оздоровленню навколишнього середовища приділялося багато уваги. Це приклад a циклічна економіка, оскільки при виробництві олії з соняшників їх лушпиння може використовуватися для отримання енергії виробництва. Зола, отримана при спалюванні лушпиння, є цінним комплексним мінеральним добривом і може бути надалі використовується як екологічне добриво. Метою цієї статті є оцінка енергетики та інвестицій потенціал соняшнику як внутрішнього резерву підвищення ефективності виробництва та зниження викиди вуглекислого газу. Зокрема, еквіваленти енергетичного заміщення лушпиння соняшнику оцінено витрати енергії на масложирових підприємствах, скорочення викидів вуглекислого газу. А Розглянуто узагальнену схему виробництва електроенергії з лушпиння соняшнику. Зокрема, описано використання золи лушпиння соняшнику як добрива. Дослідження показали, що лушпиння соняшнику, наявне в Україні, можна більш ефективно використовувати для виробництва електроенергії. тому стратегічні рекомендації були розроблені на основі проведеного дослідження
Keywords: sunflower; biofuel; bioresource potential; sunflower husk; fertilizers; investment; Ukraine; соняшник; біопаливо; біоресурсний потенціал; лушпиння соняшника; добрива; інвестиції; Україна; кафедра економіки і права